Pengaruh Kebiasaan Bermain Game Online terhadap Keterampilan Berpikir Kritis Peserta Didik Kelas Tinggi Sekolah Dasar - Aji Fajar Budiman; Loliyana Loliyana; Ismu Sukamto; Rapani Rapani (Universitas Lampung, 2022)
The problem of the research is the low critical thinking skill of high level students at Elementary School State 1 Fajar Mulia. The research aims to determine the effect of online gaming habits on students’ critical thinking. The research type was a quantitative with an ex-post facto method. The population consisted of 105 students and the samples were 53 of them using a probability technique sampling of proportionate stratified random sampling. The data collection technique used questionnaires and test. The data were analyzed by using a linier regression formula. The results showed that there was an effect of online gaming habits on the critical thinking skill of high level students at Elementary School State 1 Fajar Mulia with the category “low”. It means that the online gaming habits is one of the factors positively affecting on the critical thinking skill of high level students at Elementary School